Influência de diferentes materiais e diferentes técnicas de limpeza do espaço para o pino em dentes restaurados com pinos anatômicos - Fontana, Patrícia Eliana (2021)
In the present work two articles will be presented involving the use of relined glass fiber post in endodontically treated bovine teeth weakened. The first proposal, in article format, aimes to evaluate the fracture resistance of endodontically treated teeth restored with glass fiber posts relined with different materials. For this, 60 bovine incisor teeth were randomly distributed in 6 groups, according to the material used to relined the glass fiber post (One Bulk Fill, One Bulk Fill Flow, Z250 XT, Z350 XT, AllCem Core and Control - not relined). The specimens were submitted to mechanical cycling (37°C, 45°, 130 N, 2.2 Hz and 5 x 105 pulses). The specimens who survived mechanical cycling were subjected to a fracture load test at a speed of 0.5 mm/min and a slope of 45° until failure occurred. The failures were classified as unfavorable and favorable. Data were analyzed with two-way ANOVA, Tukey's and chi-square test. The One Bulk Fill Flow group presented higher resistance to fracture, followed by Z250 XT, One Bulk Fill, Z350 XT, Control and Allcem Core groups, although there was no statistically significant difference between them. Of the fractures, 51.72% were unfavorable and 48.27% favorable. Different materials used to reline glass fiber posts don’t influence in the fracture resistance of the endodontically treated teeth. Thus, the use of materials that present better versatility is the best clinical decision. The second proposal, in article format, aimed to the influence of the postspace treatments and post-endodontic waiting time on the bond strength of glass fiber post relined to root canal dentin. Eighty bovine incisor teeth were randomized into eight groups, according to postspace treatments (NaOCl 2.5% + EDTA 17%, Alcohol 99%, distilled water, diode laser) and postendodontic waiting time (24h and 6 months). The push-out test was performed, and the failures were analyzed using a stereomicroscope. To analyze the influence of post-space treatments and postendodontic waiting time, two-away ANOVA was used. The t-test was performed to compare the postendodontic waiting time with the same treatment for the post space, and one-way ANOVA to compare treatment of the post space with the same post-endodontic waiting time. The post-endodontic waiting time for groups 24 hours obtained the highest values of push-out, when compared with groups 6 months. Post-space treatment with alcohol/24hours present statistical difference with the group diode laser/24 hours. The most common failure type was between cement and root dentin. The post-space treatments and post-endodontic waiting time have influence on bond strength of glass fiber post relined to root canal dentin.